1999
DOI: 10.1590/s0074-02761999000100022
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Insecticide Resistance and Biochemical Mechanisms in a Population of Culex quinquefasciatus (Diptera: Culicidae) from São Paulo, Brazil

Abstract: To establish an insecticidal resistance surveillance program, Culex quinquefasciatus mosquitoes from São Paulo, Brazil, were colonized (PIN95 strain) and analyzed for levels of resistance. The PIN95 strain showed low levels of resistance to organophosphates [malathion (3.3-fold)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
5

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 4 publications
1
18
0
5
Order By: Relevance
“…Embora no presente trabalho não tenha sido verificado o mecanismo metabólico envolvido na resistência aos inseticidas, modificações de esterases em populações brasileiras de C. quinquefasciatus para organofosforados já foram relatadas 4,9,21 . Entretanto, para os derivados da Avermectina, que geralmente são usados como antiparasitários em bovinos, equinos e ovinos e também como pesticidas agrícolas [22][23][24] , ainda não há registros na literatura de resistência no Brasil.…”
Section: Discussionunclassified
“…Embora no presente trabalho não tenha sido verificado o mecanismo metabólico envolvido na resistência aos inseticidas, modificações de esterases em populações brasileiras de C. quinquefasciatus para organofosforados já foram relatadas 4,9,21 . Entretanto, para os derivados da Avermectina, que geralmente são usados como antiparasitários em bovinos, equinos e ovinos e também como pesticidas agrícolas [22][23][24] , ainda não há registros na literatura de resistência no Brasil.…”
Section: Discussionunclassified
“…quinquefasciatus. 3,12 Têm sido observados marcadores cromossômicos de amplificação dos genes de esterases, associados à resistência aos organofosforados nas linhagens UNI-R1 e UNI-R2 (Campos et al 6 2001). Em função das pequenas diferenças, entre as duas populações, nas respostas ao temephos e da sobreposição dos intervalos de confiança, pode-se considerar que não há diferença entre as concentrações letais das linhagens.…”
Section: Métodosunclassified
“…12 Essa mesma espécie mostrouse ainda resistente no Rio de Janeiro 9 e em São Paulo. 2,3 Segundo indicação da Organização Mundial da Saúde, a concentração diagnóstico de temephos para larvas de Cx. quinquefasciatus é de 0,002 ppm.…”
Section: Introductionunclassified
“…Our study on resistance of Culex pipiens to fenitrothion showed high levels compared to other studies on different mosquitoes in the world [16][17][18]. In addition to the treatments carried out in vector control, arthropod vectors are also subjected, depending on their ecology, to the insecticidal pressure resulting from agriculture or domestic uses, thus accelerating the appearance of the phenomenon and the spread of resistant alleles in the vector populations, resulting in a loss of effectiveness of the treatments.…”
Section: Discussionmentioning
confidence: 63%